HUBUNGAN DRUG RELATED PROBLEMS (DRPs) KATEGORI DOSIS OBAT AMLODIPIN DAN KAPTOPRIL TERHADAP KONDISI TEKANAN DARAH PADA PASIEN HIPERTENSI - Husnatika; Nurmainah; Rizkifani, Shoma (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
The incidence of drug-related problems (DRPs) in the dose category on the use of antihypertensive drugs has been associated with the failure of the patient's optimal blood pressure target. The study aims to analyze the relationship between drug-related problems (DRPs) on administering amlodipine and captopril drugs to the blood pressure conditions of elderly hypertensive patients in Puskesmas. This research is observational research with a cross-sectional design of analytical nature—purposive sampling techniques. The total number of samples meeting the inclusion and exclusion criteria was 435 patients. Analysis of DRPs dose category relationship data on administration of amlodipine and captopril against blood pressure conditions using a chi-square test. The results of the study showed that the characteristics of patients visited tended to be aged 65-69 years (53.33%), female (68,51%), stage II hypertensive (62.1%), amlodipine (80.92%). The incidence of the DRP dose category in stage II hypertensive (7.6%). Statistically known DRPs of amlodipine and captopril dosing categories showed different significance in each patient's condition of prehypertension (p=0.260), hypertension stage I (p = <0,001), hypertensive stage II (p<0,001). This study concludes, there is a relationship between the incidence of DRPs in the dose category in patients with stage I and stage II hypertension.